2018
DOI: 10.1039/c7dt03035e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Eu(iii) acetylacetonate-doped well-defined titania particles with efficient photoluminescence properties

Abstract: The aggregation/dispersion of luminescent species is a critical factor that determines their luminescence properties. In this study, europium(iii) acetylacetonate (Eu(acac)) was doped into a titania matrix to form Eu(acac)-doped titania particles with well-defined size and shape through a microreactor-based sol-gel approach. The morphology and structure of the as-synthesized products were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…It is evident that the crystal lattice distortion rises with doping, as we predicated because of insertion of Eu +3 ions into the TiO 2 structure. Similar results were observed by Pal .et al 39 The microstrain (ε) of the prepared un doped and TiO 2 : Eu 3+ thin films can be calculated from the relation (13): 40 (13) It is observed that microstrain decrease with increasing doping concentration, which imply decrease in defect, is due to the motion of the interstitial atoms from their grain boundary to the crystals.…”
Section: Electrical Studiessupporting
confidence: 80%
See 1 more Smart Citation
“…It is evident that the crystal lattice distortion rises with doping, as we predicated because of insertion of Eu +3 ions into the TiO 2 structure. Similar results were observed by Pal .et al 39 The microstrain (ε) of the prepared un doped and TiO 2 : Eu 3+ thin films can be calculated from the relation (13): 40 (13) It is observed that microstrain decrease with increasing doping concentration, which imply decrease in defect, is due to the motion of the interstitial atoms from their grain boundary to the crystals.…”
Section: Electrical Studiessupporting
confidence: 80%
“…However, Amorphous titania particles doped with Eu(III) acetylacetonate with atypical molar Eu/Ti ratios are elaborated at concentration of Eu = 0.125, 0.5, 2.0 and 5.0 using sol gel method was studied. 13 It was observed that ideal Eu/Ti value (0.5) that displayed greatest luminescence. Moreover, the Eu (acac) 3 doping is suitable for optoelectronic, organic, and environmental purposes.…”
mentioning
confidence: 96%
“…To meet all these demands, fluorescent nanoporous amorphous titania submicron particles with a narrow particle size distribution can be a promising DDS carrier. Titania is known as a bioinert ceramic and thus has been used for biomedical applications through the formation of a nanoporous structure which allows for accommodating fluorescent species. In general, DDS carriers are required to be water dispersible at around the biological pH range (pH = 7) and to achieve the controlled release of drug molecules.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this barrier, we have employed a microfluidic technique which enabled us to obtain well-defined titania–octadecylamine (ODA) hybrid submicron particles containing various functional units. More specifically, the titania–ODA hybrid particles have been functionalized with such species as fluorescein, iron­(III) acetylacetonate, and europium­(III) acetylacetonate (Eu­(acac) 3 ) . Furthermore, ODA is removed from the hybrid particles to form nanoporous amorphous titania submicron particles and realize the improved dispersibility in biological solution .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation